Two sides of the stream: the politics of belonging between foreign ex-farm workers and A1 farmers on a fast track farm in Zimbabwe - Patience Chadambuka; Kirk Helliker (Taylor and Francis Group, 2023)
Zimbabwe’s Fast Track Land Reform Programme continues to attract scholarship on land and agrarian reform. The farm occupations by black Zimbabweans and subsequent displacements of white farmers and their labourers, which conditioned the emergence of fast track, impacted significantly the former farm workers, as they had to reinvent their lives thereafter. Issues focusing on livelihoods and belonging became pertinent to ex-farm workers, particularly those of foreign origin. Zimbabwean-by-origin ex-farm workers could relocate to their communal areas, but this was not an easy option for those of foreign origin. This article focuses on farm workers of foreign origin who remained on former white-owned commercial farms after fast track by examining their contested belonging with autochthonous occupiers and, later, new A1 fast track farmers. Fieldwork entailed ethnographic research on an A1 farm in Shamva District, Mashonaland Central Province. Those considering themselves as autochthones (A1 farmers) tried to impose hegemonic control over the ex-farm workers (labelled as allochthones). Despite the exclusionary stratagems imposed on them, ex-migrant workers also stamp their autonomy and belonging on fast track farms in Zimbabwe.